Pullout Behavior of Titanium Alloy Reinforcing Bars in Ultra-High Performance Concrete - Mahesh Acharya; Jared Cantrell; Mustafa Mashal (Engineering Proceedings, 2023)
This paper presents the novel concept of titanium alloy reinforced ultra-high performance concrete (TARUHPC) that can be utilized in bridges. This research highlights the advantages associated with titanium alloy bars (TiABs) and ultra-high performance concrete (UHPC). To validate the concept, pullout tests were implemented to assess the pullout behavior of TiABs with concrete and UHPC. Twelve beam samples (normal concrete and UHPC) were prepared using #6 (ø 0.75 inch) TiABs with different embedment lengths. TARUHPC specimens performed exceedingly better, with an average ultimate force of about 29 kips and a resulting shear stress of 1.82 ksi.